AS REPRESENTAÇÕES SOCIAIS DOS ALUNOS, PAIS E PROFESSORES SOBRE O PROCESSO DE ENSINO E APRENDIZAGEM DE INGLÊS - Pallú, Nelza Mara (2008)
The English language (EL) today in its condition of lingua franca represents an opening to the technological and scientific development process and social democratization of our country. So, the teaching and learning context needs to be in harmony with this reality. That demands, besides the different issues that involve working with a foreign language, discussed in this work, to keep a dialogue among all the participants of this educational process. Considering that society builds representations on the role of a foreign language (FL), we presented a research whose objectives were to know and to analyze the social representations of the participants of the English Teaching and Learning process. Conducted by the theoretical referential of Social Psychology (Moscovici), Critical Pedagogy (Giroux, McLaren), Critical Linguistics (Fairclough, Meurer, Rajagopalan) and the Theory of Social Discourse (Foucault), whose understanding for the work with a FL are complemented in social-interactionist-discursive perspectives, in this research we looked for a dialogue with students, parents and teachers of public and private schools of Elementary School. Therefore, the methodological approach adapted was qualitative-quantitative and the collected data through an application of 452 questionnaires, whose analysis resulted in the identification of eighteen (18) social representations on English importance for life, for society and in the school. From those, five (05) representations which compound the Central Nucleon (CN), were described and analyzed under the Content Analysis (CA) and also the Critical Analysis of Speech (CAS) methodologies, focusing an imaginary influenced by the Communicative Approach of teaching of FL and by economic neo liberalist conceptions. The thirteen (13) representations which compound the Peripheral Nucleon (PN) show emergent situations of EL demanding, as a language that permeates global relations that still need to be discussed and questioned into the educational context in order to have better results. We expect with the research to propitiate subsidies for a reflection about the social representations and their importance for the English Teaching and Learning Process.